PERAN TEKNOLOGI INFORMASI DALAM MENDUKUNG PENERAPAN AUDIT BERBASIS RISIKO DI PEMERINTAH KABUPATEN TOBA - Gaol, Lasando Lumban (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2024)
This study aims to analyze the implementation of information technology in risk-based audits in the Toba Regency Government. The research method used is qualitative, with data collection techniques through in-depth interviews, observations, and document analysis. Interviews were conducted with five informants, consisting of the Head of the Supervision Division, Senior Auditor, Junior Auditor, First Auditor, and Supervision Staff.The results of the study indicate that information technology has been applied in the planning, implementation, and reporting stages in the Toba Regency Government, which helps improve efficiency and accuracy in these processes. However, the implementation of information technology in the supervision function is still not optimal and is mostly carried out manually. The main challenges faced include infrastructure limitations, lack of technical competence among auditors, and resistance to change from conventional to digital methods.The implications of this study include practical suggestions for local governments to improve information technology infrastructure, provide continuous training for auditors and IT staff, and reduce resistance to change through proper education. Academically, this research adds to the literature on the use of information technology in risk-based audits in local governments and can serve as a reference for further research on the implementation strategies of information technology in government supervision.